Pengaruh Tata Kelola Perusahaan dan Pertumbuhan Penjualan Terhadap Pajak Agresif Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Syamsidar; Emmi Suryani Nasution; Rizki Munazar (Jurnal EMT KITA, 2022)
This study aims to examine the effect of corporate governance and sales growth on corporate tax aggressiveness. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2019. This study included all 111 populations as research observations. The data used is balanced panel data, then analyzed using the Panel Least Squares (PLS) method and the Common Effect Models (CEM) test. The results of this study found that corporate governance and sales growth have an effect on reducing tax aggressiveness, but not significantly.